Siblings with Rett Syndrome: A fatal male case and an asymptomatic female carrier - José M. Lazaro-Guevara; Karen M. Garrido-Lopez (Rare)
Background: Rett Syndrome (RTT) is an X-linked dominant neurodevelopmental disorder, primarily affecting females. It was previously believed that male cases, although rare, frequently result in severe symptoms and early mortality due to hemizygosity of the X chromosome. However, recent studies show that some males with MECP2 variants may present with a broad phenotypic spectrum, including milder forms, as well as a broader spectrum in affected females due to the effect of X-inactivation that previously was underrecognized. Case presentation: We report RTT in two siblings from the same parents, both carrying a pathogenic MECP2 mutation (c.763 C>T, p.Arg255*). The male sibling presented early hypotonia, profound developmental delays, and died in infancy. Initially presumed to be a de novo mutation, subsequent expanded genetic testing revealed the mother to be an asymptomatic carrier—likely attributable to favorable or skewed X chromosome inactivation. She had inherited this mutation neither from her father nor her mother, as both maternal grandparents tested negative. Despite two in vitro fertilization (IVF) attempts with preimplantation genetic diagnosis (PGD) in Guatemala (ultimately unsuccessful), the couple conceived naturally. Their female child, who carries the same MECP2 mutation, remains asymptomatic at 27 months, demonstrating typical developmental milestones. Conclusion: These findings underscore the broad phenotypic spectrum of RTT, with markedly different clinical outcomes—for this specific case fatal in the hemizygous male and asymptomatic in the female carrier. They also highlight critical considerations for genetic counseling, the financial and emotional challenges inherent in assisted reproductive technologies in resource-limited settings, and the importance of ongoing surveillance for carriers of MECP2 mutations due to risk of developing subtle or late-onset features.